Les maisons des Noirs marrons de Guyane - Marie-Pascale Mallé (In Situ)
By the Maroni river, which is the border beetwen French and Dutch Guyanas, live the Aluku and the Djuka, descendants from marroon slaves escaped from Suriname plantations. Far from european settlers, they developped original cultures, which mixed african traditions and Amerindian elements. In spite of recent changes in the way of life, their architecture is still a testimony of their original history.